Freud as a social and cultural theorist : on human nature and the civilizing process - Kaye, Howard L., 1951- (New York : Routledge, 2019)
This book offers a new account of Freud's work by reading him as the social theorist and philosopher he always aspired to be, and not as the medical scientist he publicly claimed to be. In doing so, the author demonstrates that's Freud's social, moral, and cultural thought constitutes the core of his life's work as a theorist, and is the thread that binds his voluminous writings together: from his earliest essays on the neuroses, to his foundational writings on dreams and sexuality, and to his far-ranging reflections on art, religion, and the dynamics of culture. Returning to the fundamental questions and concerns that animate Freud's work - the nature of evil; the origins of religion, morality, and tradition; and the looming threat of resurgent barbarism - Freud as a Social and Cultural Theorist provides the first systematic re-examination of Freud's social and cultural thought in more than a generation. As such, it will be of interest to social and cultural theorists, social philosophers, intellectual and cultural historians, and those with interests in psychoanalysis and its origins.
OCLC-licensed vendor bibliographic record.
Keywords: Freud, Sigmund, -- 1856-1939 -- Political and social views; Psychology -- Social aspects; PSYCHOLOGY / Reference; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General